Uji Aktivitas Antibakteri Ekstrak Kental Tanaman Pisang Kepok Kuning (Musa paradisiaca Linn.) terhadap Staphylococcus aureus dan Escherichia coli - Ayu Putri Ningsih; - Nurmiati; Anthoni Agustien (Jurnal Biologi Universitas Andalas, 2013)
Antibacterial activity of crude extracts of pisang kepok kuning plants (Musa paradisiaca Linn.) were tested against Staphylococcus aureus and Escherichia coli. Roots, corms, pseudoterms, flowers, and ripe fruits of pisang kepok kuning cultivar were macerated with ethanol 96% and evaporated in a rotary evaporator at 50C. All of crude extracts were screened for its antibacterial activity by using Agar Well Diffusion Method with concentration based on 200 grams of fresh weight. This research used Completed Randomized Design (CRD) with nested pattern, four replications, and consist of two factors. First factor was bacteria and the second factor was crude extracts of pisang kepok kuning such as roots, corms, pseudoterms, flowers, and ripe fruits. The results showed that all of crude extracts have significant antibacterial activity against S. aureus and E. coli. Crude extract of the corm has highest antibacterial activity against S. aureus with diameter of inhibition area was 20,391 mm with inhibition zone type isirradical and diameter inhibition area 18,962 mm for E. coli that has radical zone.Keywords : Musa paradisiaca Linn., S. aureus, E. coli, antibacterial